Meningkatkan Aktivitas, Keterampilan Membaca Pemahaman, Dan Hasil Belajar Siswa Bahasa Indonesia Menggunakan Model Pbl, Circ, Dan Picture And Picture Kelas Iv Di Sdn Kelayan Selatan 10 Banjarmasin - Siti Norhalisa; Suhaimi . (CV. ITTC INDONESIA, 2024)
The problem of this study is the low activity, students' reading comprehension skills, and student learning outcomes in class IV SDN Kelayan Selatan 10 which are caused by learning that is not fully student-centered, monotonous and less fun learning, and reading activities that have not been carried out optimally. Therefore, an alternative to solving the problem is to use a combination of Problem Based Learning, Cooperative Integrated Reading Composition, dan Picture And Picture models in learning. The purpose of this study is to describe teacher activities, student activities, and to analyze the improvement of students' reading comprehension skills and learning outcomes. This research used Classroom Action Research (CAR), conducted in 4 meetings in class IV SDN Kelayan Selatan 10 with a total of 24 students. Data were analyzed based on the results of observations of teacher activities, student activities, reading comprehension skills, and student learning outcomes with descriptive techniques, described in the form of tables and graphs, interpreted using criteria on each indicator of the success of teacher activities, student activities, student reading comprehension skills, and the achievement of individual and classical student learning completeness. The results of this study showed that the teacher's activity increased to a score of 28 with very good criteria. In classical student activity, it also increased to 100% with very active criteria. The students' reading comprehension skill classically also increased which was 92% with very skillful criteria. Students' cognitive learning outcomes increased to 100% with complete criteria. Students' affective learning outcomes increased to 100% with complete criteria. Psychomotor learning outcomes increased to 92% with complete criteria. Based on the results of the study, it is concluded that using the Problem Based Learning, Cooperative Integrated Reading Composition, dan Picture And Picture Model can improve students' Reading Comprehension Skills in Class IV SDN Kelayan Selatan 10. It is recommended that using this model can be used as an alternative in increasing student activity which has an impact on improving student learning outcomes.